Siti Khadijah RA: Implementasi Prinsip Etika Islam Pengusaha Wanita - Mais, Rimi Gusliana; Wulaningsih, Ririn Widyastuti (ITB AAS INDONESIA Surakarta, 2024)
Siti Khadijah RA's Islamic entrepreneurial spirit is the basis for this article. The aim is to study how modern entrepreneurial women behave. This was the only Islamic educational tradition during the time of the Prophet where women served together. The aim of this research is to create an entrepreneur in the style of Siti Khadijah RA as an example of Muslim women who were successful in business in history as a solution for today's female entrepreneurs and spread this entrepreneurship throughout the world. Siti Khadijah RA, wife of the Prophet Muhammad (pbuh), was one of the most famous female traders due to her success as a respected and wealthy business woman of her time using Islamic Business Ethics. Women do many important things in life. Women are not just teachers, but also a source of family love. In the modern world, the differences in roles between men and women are gradually decreasing. Many women work in important positions. Many women work in important government positions. Moreover, the majority of modern entrepreneurs are women. Women became more important after Islam entered Arabia. Women are given the opportunity to participate in business and demonstrate their abilities in society. As a data source for this research, literature research was used and relevant scientific articles were studied. The results of this research contain a number of basic verses in the Koran regarding entrepreneurship. Muslim entrepreneurs not only pay attention to the definition of entrepreneurship, but also social entrepreneurship.